A dose calculation algorithm with correction for proton-nucleus interactions in non-water materials for proton radiotherapy treatment planning. (26th November 2015) - Inaniwa, T; Kanematsu, N; Sato, S; Kohno, R
Abstract: In treatment planning for proton radiotherapy, the dose measured in water is applied to the patient dose calculation with density scaling by stopping power ratio . Since the body tissues are chemically different from water, this approximation may cause dose calculation errors, especially due to differences in nuclear interactions. We proposed and validated an algorithm for correcting these errors. The dose in water is decomposed into three constituents according to the physical interactions of protons in water: the dose from primary protons continuously slowing down by electromagnetic interactions, the dose from protons scattered by elastic and/or inelastic interactions, and the dose resulting from nonelastic interactions. The proportions of the three dose constituents differ between body tissues and water. We determine correction factors for the proportion of dose constituents with Monte Carlo simulations in various standard body tissues, and formulated them as functions of their for patient dose calculation. The influence of nuclear interactions on dose was assessed by comparing the Monte Carlo simulated dose and the uncorrected dose in common phantom materials. The influence around the Bragg peak amounted to −6% for polytetrafluoroethylene and 0.3% for polyethylene. The validity of the correction method was confirmed by comparing the simulated and corrected doses in the materials. The deviation was below 0.8% for all materials. The accuracy of the correction factors derived with Monte Carlo simulations was separately verified through irradiation experiments with a 235 MeV proton beam using common phantom materials. The corrected doses agreed with the measurements within 0.4% for all materials except graphite. The influence on tumor dose was assessed in a prostate case. The dose reduction in the tumor was below 0.5%. Our results verify that this algorithm is practical and accurate for proton radiotherapy treatment planning, and will also be useful in rapidly determining fluence correction factors for non-water phantom dosimetry.